2021
DOI: 10.1111/tid.13593
|View full text |Cite
|
Sign up to set email alerts
|

A case report of tigecycline induced acute pancreatitis in a renal transplant patient and review of the literature: Should we avoid tigecycline in patients on calcineurin inhibitors?

Abstract: Tigecycline is the first member of the glycylcycline family to be approved by the U. S. Food and Drug Administration to be used in complicated skin and soft tissue infections, complicated intra-abdominal infections, and community-acquired pneumonia due to its broadspectrum antibiotic activity. It inhibits bacterial protein synthesis via binding to the 30S ribosomal subunit. The main route of resistance against tetracycline is through the efflux pump. 1,2 This mechanism makes tigecycline preferable for the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Nison Badalov et al [ 5 ] classified drug-induced pancreatitis into four classes of drugs based on the level of evidence. According to this, tigecycline can be categorized under class I drug where there is at least 1 case report describing the recurrence of pancreatitis after rechallenging with the drug [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nison Badalov et al [ 5 ] classified drug-induced pancreatitis into four classes of drugs based on the level of evidence. According to this, tigecycline can be categorized under class I drug where there is at least 1 case report describing the recurrence of pancreatitis after rechallenging with the drug [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…After renal transplantation, only three cases of AP caused by TGC or FK-506 have been reported: (1) A patient who was treated with TGC for perianal cellulitis developed AP on the tenth day of treatment. After discontinuation of TGC, the patient experienced a second episode of AP on the third day of re-treatment for a complicated abdominal infection ( Yazirli et al., 2021 ). (2) A woman developed a donor-derived carbapenem-resistant A. baumannii (CRAB) infection.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that FK-506 may interact with TGC, and the use of TGC may lead to an elevated serum FK-506 concentration, which subsequently decreases after discontinuation of TGC ( Pavan et al., 2011 ; Chow et al., 2020 ; Yazirli et al., 2021 ). FK-506 is metabolized by the cytochrome P450 3A4 (CYP3A4) enzyme, and TGC is not a substrate, inhibitor, or inducer of the common cytochrome P450 enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…After the publication of this document, a single‐center retrospective study found that SOT recipients with polymicrobial IAI treated with tigecycline were less likely to achieve favorable clinical outcomes and experienced more adverse events (AEs) than comparator broad‐spectrum agents 103 . On the other hand, KT recipients on CNIs may be at an increased risk of developing tigecycline‐induced acute pancreatitis 104–106 …”
Section: Therapeutic Options For Esbl‐e and Cre Infections In The Sot...mentioning
confidence: 99%
“…103 On the other hand, KT recipients on CNIs may be at an increased risk of developing tigecycline-induced acute pancreatitis. [104][105][106] Despite its five decades of existence, fosfomycin has recently regained attention due to its unique mode of action-the irreversible inhibition of the first cytoplasmic step of peptidoglycan synthesis-that results in a potent bactericidal activity with minimal cross-resistance with other classes of antibiotics. 107,108 A non-negligible proportion of ESBL-E and CRE isolates remain susceptible, 109 although decreasing rates are being gradually reported.…”
Section: Non β-Lactam Alternativesmentioning
confidence: 99%